Implementing lightweight reservation protocol for mobile network using hybrid schema - Gani, Abdullah; Yang, L.; Anuar, N.B.; Zakaria, O.; Taher, R.S. (2009)
This paper presents our method to improve lightweight reservation protocol. This was inspired by the ever increasing volume of multimedia traffic over the Internet which demanding quality of service beyond the traditional best-effort. The Integrated Services model relies on the Resource reservation Protocol (RSVP) for signaling and reserving resources. RSVP uses the receiver-initiated reservation mechanism to set up the reservation which executes protocol complexity and incurs additional processing and storage overheads on the routers. Due to heavyweight characteristic, many researchers changed the focus to the lightweight reservation protocol. In this paper, we propose a lightweight signaling protocol of Sender-initiated and Mobility-support Reservation Protocol (SMRP) with Crossover Router (COR) as an extension to SMRP. COR scheme cannot provide smooth handover as it affects the SMRP in Mobile hosts. This is the main disadvantage of COR scheme. Pointer Forwarding Scheme makes an advance resource reservation only a forwarding one-step path from the sender along the forwarding chains. In order to make SMRP more suitable for Mobile hosts, we propose a hybrid method combining the advantages of COR scheme with Pointer Forwarding scenarios. We use ns2 Java version network simulator to test it. We evaluate the performance of SMRP in a mobile network environment. The results show that the hybrid scheme can support seamless and also efficient SMRP path rerouting during handoff in respect of decreased the drop probability.